Immobilization of HPW on UiO-66-NH2 MOF as efficient catalyst for synthesis of furfuryl ether and alkyl levulinate as biofuel - Mulik, Nagesh; Bokade, Vijay (Molecular Catalysis, 2022)
Phosphotungustic Acid (HPW) is an inorganic super acid, that is highly soluble in polar solvents limiting its applicability as acid catalysis. To overcome these limitations immobilization of HPW was carried out at room temperature by protonation of-NH2 group of UiO-66-NH2 MOF to UiO-66-NH2-HPW. ATR-FTIR spectroscopy and XPS results confirmed the protonation and chemical interaction between HPW and UiO-66-NH2. STEM-EDS mapping showed homogeneous distribution of HPW on UiO-66-NH2. BET and NH3-TPD confirmed the reduction in specific surface area, total pore volume, and increase in total acidity for UiO-66-NH2-HPW. Further, powder XRD, SEM, and HR-TEM prevailed that there is no change in phase and morphology after post-synthetic modification of UiO-66-NH2. The prepared catalyst is found to be effective for etherification and alcoholysis of furfuryl alcohol (FALc) to Furfuryl ether (FE) and Alkyl levulinate (AL). UiO-66-NH2-HPW has shown 97 mol % FALc conversions in ethanolic media and 31 mol% Ethyl furfuryl ether (EFE) yield and 29 mol% Ethyl lev-ulinate (EL) yield. UiO-66-NH2-HPW is also found to be efficient for the multistep conversion of Furfural (FFR) to FALc, FE, and AL.
Keywords: Alcoholysis; etherification; Immobilization; Phosphotungstic acid; UiO-66-NH2-HPW

Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment